2005
DOI: 10.1002/j.1556-6978.2005.tb01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Building Multicultural Competencies in School Counselor Trainees: An International Immersion Experience

Abstract: The authors describe an international cultural immersion field experience, make recommendations for counselor educators who want to establish a similar program, and present an example of a student's reflection on the experience as recorded in the personal multicultural competency portfolio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 10 publications
3
52
0
Order By: Relevance
“…Researchers (e.g., Alexander et al, 2005;Barden & Cashwell, 2014;Burnett et al, 2004;Canfield, Low, & Hovestadt, 2009;TomlinsonClarke & Clarke, 2010) have reported positive benefits of immersion experiences in developing helping professionals. However, results have been primarily qualitative and/or relied on anecdotal evidence such as participants' journals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Researchers (e.g., Alexander et al, 2005;Barden & Cashwell, 2014;Burnett et al, 2004;Canfield, Low, & Hovestadt, 2009;TomlinsonClarke & Clarke, 2010) have reported positive benefits of immersion experiences in developing helping professionals. However, results have been primarily qualitative and/or relied on anecdotal evidence such as participants' journals.…”
Section: Discussionmentioning
confidence: 96%
“…CI requires facilitators to create a safe environment in which counselors can challenge their existing worldviews and assumptions (Arthur & Achenbach, 2002;Barden & Cashwell, 2013;Paige et al, 2009). Group facilitators often engage trainees in educational group discussions regarding the larger socio-political-historical context of the communities in which trainees are immersed, and cultural values, beliefs, practices, and so on that individuals have encountered in the field (Alexander et al, 2005;Ishii et al, 2009), affording trainees a greater breadth and depth of understanding about the cultural context in which one is immersed. In addition to understanding content, CI positions trainees to experience being a culturally diverse "other," illustrating the struggles for minority clients and underscoring the influences of culture on behavior and the need for helping professionals to be culturally sensitive (Chung & Bemak, 2002).…”
Section: Cultural Immersionmentioning
confidence: 98%
See 1 more Smart Citation
“…Counselor educators have widely expressed concerns about the challenges of facilitating race-related learning in the classroom (Alexander, et al, 2005;DayVines, et al, 2007;Estrada, et al, 2004;Fier & Ramsey, 2005;Rothschild, 2005;Swigonski, 1999). Student resistance due to anxiety regarding racial dialogue is specifically discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Counselor educators are challenged to prepare counselors for racial and ethnic interaction. However, counselor educators report that facilitating educational experiences to address racism can be fraught with challenges (Alexander, Kruczek, & Ponterotto, 2005;Day-Vines, et al, 2007;Estrada, Frame, & Williams, 2004;Fier & Ramsey, 2005;Rothschild, 2003;Watt et al, 2009). Many of the challenges discussed were related to student anxiety and resistance to race-related dialogue.…”
Section: Race Obsession-avoidance Paradox: a Model For Multicultural mentioning
confidence: 99%